Bardet–Biedl Syndrome ciliopathy is linked to altered hematopoiesis and dysregulated self‐tolerance. (11th January 2021) - Tsyklauri, Oksana; Niederlova, Veronika; Forsythe, Elizabeth; Prasai, Avishek; Drobek, Ales; Kasparek, Petr; Sparks, Kathryn; Trachtulec, Zdenek; Prochazka, Jan; Sedlacek, Radislav; Beales, Philip; Huranova, Martina; et al.
Abstract: Bardet–Biedl Syndrome (BBS) is a pleiotropic genetic disease caused by the dysfunction of primary cilia. The immune system of patients with ciliopathies has not been investigated. However, there are multiple indications that the impairment of the processes typically associated with cilia may have influence on the hematopoietic compartment and immunity. In this study, we analyze clinical data of BBS patients and corresponding mouse models carrying mutations in Bbs4 or Bbs18 . We find that BBS patients have a higher prevalence of certain autoimmune diseases. Both BBS patients and animal models have altered red blood cell and platelet compartments, as well as elevated white blood cell levels. Some of the hematopoietic system alterations are associated with BBS‐induced obesity. Moreover, we observe that the development and homeostasis of B cells in mice is regulated by the transport complex BBSome, whose dysfunction is a common cause of BBS. The BBSome limits canonical WNT signaling and increases CXCL12 levels in bone marrow stromal cells. Taken together, our study reveals a connection between a ciliopathy and dysregulated immune and hematopoietic systems. SYNOPSIS: Bardet‐Biedl Syndrome is a pleiotropic genetic disease caused by the dysfunction of primary cilia. BBS is associated with altered hematopoiesis and homeostasis of the immune system in patients and mouse models. Patients suffering from Bardet‐Biedl Syndrome are prone to autoimmunity. Bardet‐Biedl patients and corresponding mouse models show altered hematopoiesis and homeostasis of blood cells. Development and homeostasis of B cells in mice are regulated by the BBSome transport complex. Obesity and reduced production of CXCL12 in bone marrow stromal cells cause these hematopoietic alterations. Abstract : Bardet‐Biedl Syndrome is a pleiotropic genetic disease caused by the dysfunction of primary cilia. BBS is associated with altered hematopoiesis and homeostasis of the immune system in patients and mouse models.